Storage assignment policies for a movable rack system served by a single storage and retrieval machine - Pornchai Paopahon; Pandey, P.C.; Afzulpurkar, Nitin V.; Pastijn, H. (Bangkok : Asian Institute of Technology, 1997)
Use of Automated storage and retrieval systems (AS/RSs) in manufacturing companies involves high initial investment. In order to reduce this cost sometimes a movable rack system served by a single S/R machine (MRSS) can be employed. This would increase the warehouse floor space utilization better than a typical AS/R system with multiple fixed aisles. The objective of this study is mainly related to a comparison between the operating performance (throughput and utilization of warehouse) of three storage assignment policies: pure randomized assignment; closest-open-location assignment and three class-based assignment, using a movable rack system (MRSS) and a fixed rack system (MASS). Simulation models for the hypothetical warehouse employing MRSS and MASS system are developed to predict performance of the warehouse in each case. The results demonstrate that significant increase in throughput for both MRSS and MASS system are obtainable from the use of three class-based storage assignment policy. Furthermore, a MRSS system with pure randomized and closest-open-location policies gives better performance than MASS system. Whereas with three class-based storage policy both systems perform well.
Thesis (M.Eng.) - Asian Institute of Technology, 1997
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Advanced Technologies
Keywords: Warehouses -- Management; Storage racks